2022
DOI: 10.1186/s12870-022-03704-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression VaPYL9 improves cold tolerance in tomato by regulating key genes in hormone signaling and antioxidant enzyme

Abstract: Background Abscisic acid (ABA) has been reported in controlling plant growth and development, and particularly dominates a role in resistance to abiotic stress. The Pyrabactin Resistance1/PYR1-Like /Regulatory Components of ABA receptors (PYR1/PYL/RCAR) gene family, of which the PYL9 is a positive regulator related to stress response in ABA signaling transduction. Although the family has been identified in grape, detailed VaPYL9 function in cold stress remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 84 publications
(96 reference statements)
2
8
0
Order By: Relevance
“…Heatmap of transcript levels for genes and contents for metabolites that are involved in the biosynthesis of phenylpropanoids. signaling pathway, and previous studies reported that PYL genes are positive regulators related to stress response in ABA signaling transduction, such as PYL4 and PYL9 (Nai et al, 2022;Ren et al, 2022). In our study, we found that three PYR/PYL genes (c25218.graph_c0, c34730.graph_c0, and c49758.graph_c0) were significantly induced by cold treatment (Figure S18a), which suggested that the ABA signaling pathway plays an important role in the response of V. sativa to cold stress.…”
Section: Plant Hormones Involved In the Response Of V Sativa To Cold ...supporting
confidence: 76%
See 1 more Smart Citation
“…Heatmap of transcript levels for genes and contents for metabolites that are involved in the biosynthesis of phenylpropanoids. signaling pathway, and previous studies reported that PYL genes are positive regulators related to stress response in ABA signaling transduction, such as PYL4 and PYL9 (Nai et al, 2022;Ren et al, 2022). In our study, we found that three PYR/PYL genes (c25218.graph_c0, c34730.graph_c0, and c49758.graph_c0) were significantly induced by cold treatment (Figure S18a), which suggested that the ABA signaling pathway plays an important role in the response of V. sativa to cold stress.…”
Section: Plant Hormones Involved In the Response Of V Sativa To Cold ...supporting
confidence: 76%
“…A total of 16 DEGs related to ABA signal transduction were obtained in the present study, and the expression level of most genes was induced during cold treatment except for three genes (Figure S17a). The pyrabactin resistance (PYR)/PYR‐like (PYL)/regulatory component of ABA receptor (RCAR) proteins that have been characterized as ABA receptors function as the core components in the ABA signaling pathway, and previous studies reported that PYL genes are positive regulators related to stress response in ABA signaling transduction, such as PYL4 and PYL9 (Nai et al, 2022; Ren et al, 2022). In our study, we found that three PYR / PYL genes (c25218.graph_c0, c34730.graph_c0, and c49758.graph_c0) were significantly induced by cold treatment (Figure S18a), which suggested that the ABA signaling pathway plays an important role in the response of V. sativa to cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ABA reduced the inhibitory effect of cold stress on the rate of CO 2 fixation in grape plants by stimulating the antioxidant enzyme system and alleviating cold-induced stomatal closure . Many genes are activated in response to cold stress that are likewise activated in response to ABA and osmotic stress . Overexpression of the AtABF3 gene enhances tolerance to drought and cold stress in transgenic lettuce ( Lactuca sativa ) .…”
Section: Discussionmentioning
confidence: 99%
“…45 Many genes are activated in response to cold stress that are likewise activated in response to ABA and osmotic stress. 56 Overexpression of the AtABF3 gene enhances tolerance to drought and cold stress in transgenic lettuce (Lactuca sativa). 57 Another gene ABF4/AREB2, an ABA-responsive element-binding factor and a member of the bZIP transcription factors, was likewise increased by cold.…”
Section: Vacold1mentioning
confidence: 99%
“…The constructed recombinant plasmids were co-transformed into yeast cells of strain Y2H and cultured on SD/-Leu/-Trp medium at 30°C for 3 days. Positive colonies were picked and transferred to SD/-Leu/-Trp/-Ade/-His + X-α-Gal medium to examine potential physical binding and interaction (Nai et al 2022).…”
Section: Y2h Assaymentioning
confidence: 99%